2013
DOI: 10.1007/s11892-013-0404-x
|View full text |Cite
|
Sign up to set email alerts
|

Rationale Use of GLP-1 Receptor Agonists in Patients with Type 1 Diabetes

Abstract: Clinicians and patients are rapidly adapting GLP-1 receptor agonists as efficacious and safe therapeutic options for managing type 2 diabetes (T2DM). GLP-1 receptor agonists stimulate insulin production and secretion from the pancreatic β cells in a glucose-dependent manner, improve gastric emptying, favor weight reduction, and reduce postabsorptive glucagon secretion from pancreatic α cells. GLP-1 receptor activity is impaired in patients with T2DM. GLP-1 secretion and subsequent physiologic actions in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 27 publications
0
15
0
2
Order By: Relevance
“…In addition to a-cell expansion and hyperglucagonaemia, diabetes is associated with disturbances in the insulinotropic action and especially the secretion of GLP1 (Vilsboll et al 2003, Holst 2007, Huml et al 2011, Kielgast et al 2011, Unger 2013. Recent investigations together with our unpublished observations have revealed that disturbances in the intestinal L-cell population may contribute to the loss-of-functional incretin response in diabetes (Kappe et al 2014).…”
Section: Introductionmentioning
confidence: 82%
“…In addition to a-cell expansion and hyperglucagonaemia, diabetes is associated with disturbances in the insulinotropic action and especially the secretion of GLP1 (Vilsboll et al 2003, Holst 2007, Huml et al 2011, Kielgast et al 2011, Unger 2013. Recent investigations together with our unpublished observations have revealed that disturbances in the intestinal L-cell population may contribute to the loss-of-functional incretin response in diabetes (Kappe et al 2014).…”
Section: Introductionmentioning
confidence: 82%
“…This unregulated glucagon secretion reduces the suppression of postprandial hyperglycemia and compounds glucose variability. Therefore, GLP‐1 RA therapy may exert benefit in T1D by inhibiting inappropriate glucagon secretion after a meal …”
Section: Emerging Usesmentioning
confidence: 99%
“…These include glucagon‐like peptide‐1 (GLP‐l), peptide YY and oxyntomodulin (Oxm) . In relation to this, several studies now confirm the clear, clinically relevant, beneficial antidiabetic effects of stable GLP‐1 derivatives in not only type 2, but also type 1, diabetes ; however, the possible benefits of related L‐cell secretory products, such as Oxm, have not been fully considered to date in type 1 diabetes . This might be because the mode of action of Oxm involves dual agonism of glucagon as well as GLP‐1 receptors ; however, cell‐based therapy with the immortalized enteroendocrine L‐cell cell line GLUTag has been shown to exert significant beneficial effects on body weight and metabolic control in insulin‐deficient streptozotocin (STZ)‐induced diabetic mice .…”
Section: Introductionmentioning
confidence: 99%